Manhaju al-Islami fi al-Huffaz 'ala al-Darurat al-Khamsi li al-Insani. - Ali Sayyid Abdul Hamid Yusuf As-Syimi (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2015)
The goal of Islamic Sharia is to safeguard the five essential aspects of human life: religion, soul, progeny and dignity, wealth, and intellect. To protect religion, Islam mandates its followers to adhere to the six pillars of faith, the five pillars of submission, and the principle of good manners. Islam strictly forbids killing to protect one's life. To safeguard one's progeny and dignity, Islam encourages and facilitates marriage for all and prohibits fornication. Islam prohibits theft to protect one's wealth, and it encourages individuals to engage in self-reflection and contemplate nature to safeguard their intellect.